Dispute on Execution of Criminal Confiscation Objects and General Seizures for Bankruptcy in Review from Legal Benefit - Muhammad Fathin Habibullah; Natangsa Surbakti; Aidul Fitriciada Azhari; Peggy Dian Septi Nur Angraini (Trigin Publisher, 2023)
Criminal foreclosures and general foreclosures of bankruptcy are different. Normative juridical research with statutory and case approaches. The aim is to find out and analyze criminal enforcement and bankruptcy at the same time that there was a conflict in the execution of the Pandawa Mandiri Group Savings and Loans Cooperative case (KSP Pandawa). The results of KSP Pandawa and Nuryanto's research, the chairman of KSP Pandawa went bankrupt, the decision of the Commercial Court at the Central Jakarta District Court and all assets were publicly confiscated. Nuryanto was convicted by the Depok District Court on charges of fictitious investment and an additional crime of auctioning all economic assets for the state. The Pandawa KSP Curator Team filed a lawsuit for a criminal verdict that was strengthened by the Supreme Court's Cassation Decision Number 3 K/Pdt.Sus-Bankrupt/2019. Amar Cassation requests that the Depok District Attorney hand over all confiscated assets to the Pandawa KSP Curator Team. The cassation decision fulfills legal benefits, KSP Pandawa can register receivables with the curator for verification and will receive proportional loss returns as stipulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations.